A dedução transcendental B na Crítica da Razão Pura: o problema da unidade sintética e da unidade sensível - Marques, José Luciano Verçosa (2020)
In §26 of B-Deduction of the Critique of Pure Reason, Kant states that space and time are not represented merely as forms, but as formal intuitions. Their representations presuppose a synthesis that gives them unity. The unit of this synthesis can be no other than the unit that intellectual synthesis gives to the manifold of an intuition in general, in accordance with the original synthetic unity of apperception. This condition, necessary for the development of the proof of the categories as objectively valid, brings with it two difficulties. The first difficulty concerns to the comprehension of the very intuitive nature of space and time, because, according to their metaphysical expositions, the unity of these representations plays a fundamental role in proving space and time as pure intuitions. The second difficulty concerns the status of the sensible given. Since space and time, which give the conditions under which something can be given, are represented by a synthetic unit, how then is it possible for something to be given previously and independently of a synthesis as an activity of understanding? To clarify this point, the present Thesis aims to demonstrate that space and time are only represented as pure intuitions under a determination of the understanding, wich unifies the conditions of giveness of the manifold under a synthetic unity. This activity doesn't produce the conditions of the giveness of the manifold, but only represents it under a concept of object. This means that the proper intuitive characteristic, the singularity, is not produced.In this way, the correlation marked by the codependency between understanding and sensibility must be analyzed in relation to a demonstration that requires examining the active sphere of understanding concomitantly to sensibility and vice versa. With this, we try to demonstrate that the objective representations of space and time, although they are represented by means of a synthesis, what defines them as intuitions remains and is verified as the understanding unifies their representations. In this way, it is possible to comprehend that the unification of these representations by understanding is not a necessary condition for something to be given, but only so that the given can be apprehended as an object.